Adverse Effects, Health Service Engagement, and Service Satisfaction Among Anabolic Androgenic Steroid Users. (March 2017) - Zahnow, Renee; McVeigh, Jim; Ferris, Jason; Winstock, Adam
There are a number of adverse health effects associated with the use of anabolic androgenic steroids (AAS), ranging from mood disturbances to gynecomastia and impaired sexual function. Despite the potentially serious nature of adverse effects, evidence suggests that users are reluctant to seek medical assistance. This study explores factors associated with health service engagement and treatments related to service satisfaction among a sample of AAS users. The analyses are based on a sample of 195 respondents from the Global Drug Survey 2015 who reported using steroids in the previous 12-month period and experiencing concerns about adverse health effects. The results indicate reluctance among AAS users to engage with health services, with only 35.23% reporting that they visited a doctor when experiencing concerns about adverse effects. Concern about sexual function increased the likelihood that users engaged with health services, while concern about changes in sexual organs decreased the odds of service engagement. Among AAS users who engaged with health services, individuals who received a mental health assessment or diabetes test rated the service as more helpful than those who did not; a finding that resonates with literature indicating a desire among AAS users to monitor the health impacts of their drug use and respond to issues as they arise. While more research is needed, the present results underscore a need for nonjudgmental health services aimed at assisting AAS users to monitor adverse effects and minimize harm through early intervention.